Eco-Friendly Wood Preservation Using Nano Urea to Prevent Fungal Degradation and Improve Material Durability - Muhammad Latif; Kusrin; Bambang Purnijanto; Diah Rahmawati (Tropical Aquatic and Soil Pollution, 2026)
Wood is widely used in construction due to its renewability and favorable mechanical properties; however, it is highly susceptible to fungal degradation, which reduces durability and structural performance. Conventional wood preservatives are effective but often raise environmental and health concerns because of their toxic chemical content. This study investigates the use of nano-urea as an eco-friendly wood preservative for sengon wood (Falcataria moluccana), representing one of the first studies exploring nano-urea specifically for antifungal wood protection and durability enhancement. Sengon wood samples were treated with nano-urea at concentrations of 2%, 3%, and 5%, alongside untreated control samples. Antifungal performance was evaluated through weight loss measurements, fungal growth observations, and assessment of the infected area after 12 weeks of exposure, while mechanical performance was assessed using tensile strength testing and microstructural analysis. The results demonstrated that increasing nano-urea concentration significantly reduced fungal degradation, with the 5% treatment completely inhibiting visible fungal growth. In addition, nano-urea treatment slightly improved tensile performance and produced a denser wood microstructure with reduced pore size, indicating enhanced structural compactness. These findings confirm that nano-urea is a promising sustainable alternative to conventional preservatives, offering effective biological protection while maintaining mechanical integrity. The proposed treatment also shows strong potential for scalable and environmentally responsible applications in sustainable construction and wood-based material industries.